C.S. Lewis Use of Symbol to Express Christian Concepts, Stories, and Teaching as Seen in The Chronicles of Narnia: the Magicians Nephew - Hermawan -; Adventina Putranti (Universitas Sanata Dharma, 2015)
Literature is said to be the medium where author expresses his experience in life, especially on the relationship with the creator. This idea could be clearly seen in the Chronicles of Narnia: The Magicians Nephew where C.S. Lewis, the author, expresses Christian concepts, stories, and teaching he understands throughout his life. Those all are expressed through symbolism due to its capability in making association with human experience as well as conveying any complex ideas in a form of concrete objects which are easily understood by the readers.Keywords: expressive approach, symbol, Christianity